GREEN ECONOMIC POLICIES AND PRACTICES: AN EVALUATION OF THEIR IMPACT ON SOCIO-ECONOMIC WELL-BEING IN THE CONTEXT OF CLIMATE CHANGE - Loso Judijanto; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
Green economic policies and practices have become a strategic approach to addressing the increasingly urgent challenges of climate change. This study evaluates the impact of green economic policies on socio-economic well-being, with a focus on carbon emission reduction, renewable energy use, and inclusive sustainable development methods. The evaluation results indicate that green economics not only addresses environmental issues but also makes significant contributions to job creation, improved quality of life, and economic resilience. Although these policies face various challenges, such as resistance from traditional industries and resource constraints, holistic strategies and multilateral collaboration are necessary to ensure their effective implementation. Thus, green economy has great potential to support the balance between environmental sustainability, economic growth, and social welfare amid the impacts of climate change.